(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2017)
Identification of deceased is an essential part of the post-mortem examination. Age is one of the important parameters for the identification of an individual whether the individual is alive, dead or human remains. The determination of age is needed for employment, marriage, majority, management of property, voting right, competency as witness and testamentary capacity. The significance of determination of age is most important in the criminal cases, such as rape, infanticide, juvenile delinquency and criminal responsibility. Age estimation can be done in various methods, including macroscopic examination of dental development and eruption, epiphyseal union of long bones, degeneration of pelvic articular surfaces and cranial sutures, as well as microscopic examination of long bones in histological analysis. Due to progressive development of bones, ageing of skeletons under the age of 25 can be more easily accomplished utilising the order of epiphyseal fusion in the long bones. Dental eruption is also a reliable indicator of age between infancy and 17 to 25 years. Cranial suture closure can be utilised to estimate age in living and death.